2014
DOI: 10.1111/cei.12273
|View full text |Cite
|
Sign up to set email alerts
|

Co-existence of clonal expanded autologous and transplacental-acquired maternal T cells in recombination activating gene-deficient severe combined immunodeficiency

Abstract: SummaryIt is commonly accepted that the presence of high amounts of maternal T cells excludes Omenn syndrome (OS) in severe combined immunodeficiency (SCID). We report a SCID patient with a novel mutation in the recombination activating gene (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…This made it possible for us to study the diversity of TCR-Vβ and the numbers of circulating Tregs (CD4+CD25+FOXP3+) in both cell populations, as well as to compare them with normal values. In line with our proposal, we found that: (i) the patient's autologous TCRs were more clonal and restricted than the maternally engrafted T cells, and (ii) there were large numbers of circulating Tregs in the maternally engrafted T-cell population, whereas the patient's autologous T cells had no CD4+CD25+FOXP3+ expression whatsoever (Lev et al 2014). These findings support our hypothesis that autologous and maternal cells can coexist in SCID patients.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…This made it possible for us to study the diversity of TCR-Vβ and the numbers of circulating Tregs (CD4+CD25+FOXP3+) in both cell populations, as well as to compare them with normal values. In line with our proposal, we found that: (i) the patient's autologous TCRs were more clonal and restricted than the maternally engrafted T cells, and (ii) there were large numbers of circulating Tregs in the maternally engrafted T-cell population, whereas the patient's autologous T cells had no CD4+CD25+FOXP3+ expression whatsoever (Lev et al 2014). These findings support our hypothesis that autologous and maternal cells can coexist in SCID patients.…”
Section: Introductionsupporting
confidence: 90%
“…We propose that coexisting autologous and maternal cells in patients exhibiting milder OS symptoms may simply not have been detected and not because they are mutually exclusive. Indeed, we recently had the opportunity to evaluate an unusual case of an immunodeficient SCID patient with mild OS who harbored a novel homozygous mutation in RAG1 (4-BP DEL.1406 TTGC) (Lev et al 2014). To define the patient's circulating T cells, we first studied cell function and thymic activity and found them to be severely reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal engraftment is a common feature in SCID patients; engrafted T lymphocytes contain a high fraction of functional regulatory T cells, conferring a high-tolerance capacity that appears to represent a toleration advantage beside the severe immunodeficiency. Maternal cells could provided some degree of immunity and, therefore, may protect the child from severe infections [5].…”
Section: Discussionmentioning
confidence: 99%
“…It was commonly accepted that the presence of large amounts of maternal T cells in SCID patients can only occurs if host T cells are lacking. This thought was disproved by the recent findings of long-term coexistence of engrafted maternal T cells and autologous T cells in a SCID patient with a Janus kinase (JAK) 3 mutation [9] and in a patient with mild Omenn's Syndrome phenotype [5]. In rare cases, engrafted maternal T cell might persist for long time leading to partial reconstitution of immune function and delayed clinical presentation of SCID [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation